A Bibliometric Analysis of Teacher’s Turnover Intention - Hà, Lê Vũ (Journal of Education Culture and Society, 2024)
Aim. The purpose of this article is to review past research trends and explore emerging research directions on teachers’ turnover intentions.Methods. The authors used the co-citation method and bibliometric analysis using VOS Viewer software to review 137 publications mentioning teachers’ intention to leave.Results. The results of the co-citation analysis show that there are 4 main topics, while the results of the bibliographic coupling analysis show that there are 6 main topics in the study of teachers’ intention to quit. From there, it shows that future research trends can focus on specific teacher populations more likely to consider quitting and explore how various factors influence their intentions. Improving teachers’ professional environment to reduce professional burnout and increase job satisfaction is also an interesting future research aspect.Conclusions. In conclusion, this study contributes to the understanding of the literature by classifying studies on teachers’ turnover intention and identifying significant patterns through bibliometric method. However, the study’s limitations, as analyses rely solely on citations, potentially introduce biases; the interpretation of researchers in determining topics may lead to exclusions of emerging trends due to insufficiently gathered publications.